2021
DOI: 10.4103/sja.sja_908_20
|View full text |Cite
|
Sign up to set email alerts
|

The status of medical malpractice litigations in Saudi Arabia

Abstract: Context: Medical malpractice is a leading cause of morbidity and mortality worldwide. Analyzing the current number of lawsuits and comparing it to previous years will help assess the status of medical malpractice litigations in Saudi Arabia. Subjects and Methods: A review and analysis of the annual statistics book of the Medico-Legal Committees (MLCs) in Saudi Arabia over the years (1437–1439 H) was conducted. Results: Over the 3-year study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The present study analyzed violation claims in which MOH was the plaintiff, in contrary to the overwhelming majority of previous studies that analyzed only claims involving patients as plaintiffs. 16,18,20,23,24,28,29 The study found that a majority of HCPs were found guilty (82%) and that most of them received fines as their verdicts. Previous studies found the majority of defendants involved in medical litigation in KSA not guilty.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The present study analyzed violation claims in which MOH was the plaintiff, in contrary to the overwhelming majority of previous studies that analyzed only claims involving patients as plaintiffs. 16,18,20,23,24,28,29 The study found that a majority of HCPs were found guilty (82%) and that most of them received fines as their verdicts. Previous studies found the majority of defendants involved in medical litigation in KSA not guilty.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, violation claims against the private sector showed a consistent increase throughout the years compared with the public sector. 29 Although the increased prevalence of guilty verdicts among HCPs working in the private sector could be a reflection of increased violations of the Law, it could be also a result of an increased governmental oversight over private healthcare institutions. Governmental oversight over the private sector is the responsibility of 2 entities, the Private Health Sector Department and the Compliance Enhancement Agency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fear of litigation (FoL) has been commonly recognised as an influential factor in medical decision making 7. Obstetrics is one of the leading medical specialities in terms of litigation risk and cost 8–11. FoL and defensive medicine (practice wherein a healthcare professional makes decisions out of FoL and not for the benefit of the patients) are commonly cited reasons for performing CS,12–14 sometimes without medical indication 12 15 16.…”
Section: Introductionmentioning
confidence: 99%